EFEK ANALGETIK EKSTRAK LERAK SEBAGAI BAHAN PEREDA NYERI GIGI: ANALGESICS EFFECT OF LERAK EXTRACT AS DENTAL PAIN RELIEVER - Nevi Yanti; Fitrah Utari Bakti (Dentika: Dental Journal, 2010)
Patient with root canal treatment often feels painful. Eugenol is a topical pain reliever of the most widely used in dental practice. However its cytotoxicity causes the change of inflamation at pulp tissue under it. Lerak is chosen because being expected to have analgesic effect, possibly because of flavonoid, alcaloid, saponin. This research aimed to know the analgesic effect of lerak extract on male rabbit teeth. The design of research was experimental laboratory started with obtaining the sample, 940 gr lerak extract with ethanol as solvent to get the solid extract. A total of 24 male rabbits was divided into 4 groups, with the percentage 2.5%, 5%, 7.5% and negative control (CMC 0.5%), then the rabbits were anastesized, the left and right incisors teeth of rabbit were prepared up to pulp chamber then the material was applied for 10 microlitre to each teeth, the electrode was put into the pulp chamber, the voltage was heightened by turning the voltage from 0 to the position until creating the licking reaction, the note of voltage was done from the range of 0, 5, 10, 20, 30, 40, 50 and 60 minutes. The result of research showed that the lerak extract had analgesic effect with concentrates 2.5%, 5%, 7,5%. One-way Anova showed the significant differences (p< 0.05) between CMC 0.5% and the concentration of lerak extract 2.5%, 5% and 7.5%. As conclusion, there was significant differences (p<0.05) between lerak extract 2.5% and 7.5%, but not significantly different between 2.5% and 5%, between 5% and 7,5%.